Introduction of the Water-bed Incubation Technology to Rural Poultry Farmers in Bauchi State, Nigeria - Sulaiman, A.; Hong, Peng; Nataala, A.; Jaafar , M.R.; Alkasim, Ibrahim (International Journal of Poultry Science, 2010)
The need to enhance the capacity of the rural poultry keepers is paramount to the improvement of the level of protein intake of the Nigeria populace. This would invariable have an impact on the health status of the citizenry. An obvious and effective strategy of enhancing the capacity of the rural poultry keepers is the introduction of improved techniques that are simple, appropriate, affordable and reliable. The water-bed incubator is one of such technologies hereby discussed and recommended for adoption.